A STUDY ON THE POSSIBLE ONGOING DROPOUT CAUSES OF BACHELOR IN EDUCATION THE DISTANCE - Despincieri Laham, Stelamary Aparecida [UNESP]; Lemes, Sebastiao de Souza [UNESP] (Unesp-faculdade Ciencias & Letras, 2016)
This study aimed to investigate which were the possible causes that influenced the distance learning courses dropouts from the students'perceptions. For this, it was carried out a descriptive exploratory study using a qualitative approach based on a case study about the evasion rates and causes in the course in the UAB-UFSCAR Federal University of Sao Carlos, in the Polo de Apoio Presencial of Taruma - Support Face-to-Face Unit in Taruma, a countryside town of the Sao Paulo State. The participants were the evaded students, graduated ones and attending students of the Pedagogy Licenciateship course UAB-UFSCar in the 2008, 2010, 2012 and 2013 classes. The used instruments for data collection were: a research of bibliographical review, the institution documents to ascertain the actual dropout rates, questionnaires answered by the students from mentioned classes. The contents of students' responses to the questionnaires were the basis for the survey and analysis of categories and subcategories related to Distance Education dropout. These categories and subcategories were discussed considering the theoretical framework, leading to exogenous and endogenous causes for the course evasion. Thus, the course exogenous causes were related to the external factors of the institution and the course, they are: lack of time to study, work and family demands, personal or familiar health problem. Endogenous causes were directly related to the educational institution, like: lack of tutoring communication, problems with teaching materials, interaction and interactivity in the virtual learning environment (feeling of loneliness), unsuited course design for the student's profile. The achieved results may provide support to higher education institutions which offer this modality as an indicator for the development of pedagogical projects of distance learning courses, and are concerned about the reduction of evasion incidence.
Keywords: Distance Education; Evasion; Evasion in Distance Education; Causes Evasion; Pedagogy Licenciateship in Distance Education